The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.echo.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Strain Reflects Ventriculoarterial Coupling Rather Than Mere Contractility in Rat Models of Hemodynamic Overload–Induced Heart Failure

Abstract: Background: Longitudinal strain (LS) is a sensitive marker of systolic function. Recent findings suggest that both myocardial contractility and loading conditions determine LS. The aim of this study was to investigate whether LS reflects the connection of cardiac contractility to afterload (termed ventriculoarterial coupling [VAC]) rather than mere contractility in rat models of hemodynamic overload-induced heart failure (HF). Methods: Pressure overload-induced HF was evoked by transverse aortic constriction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…In a recent publication of our research group, we have demonstrated that GLS does not correlate with LV contractility indices in rat models of VO-induced and PO-induced HF, rather reflecting VAC. 9 Therefore, GLS carries similar shortcomings to the conventional measures of LV function with its considerable load sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication of our research group, we have demonstrated that GLS does not correlate with LV contractility indices in rat models of VO-induced and PO-induced HF, rather reflecting VAC. 9 Therefore, GLS carries similar shortcomings to the conventional measures of LV function with its considerable load sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that STE‐derived strain parameters are significantly influenced by loading conditions 7,8 . In a recent study by our research group using rat models of pressure (PO)‐induced and volume overload (VO)‐induced heart failure (HF), GLS did not show a relationship with LV contractility, rather reflecting ventriculo‐arterial coupling (VAC) 9 . These observations substantially affect the interpretation of deformation parameters in haemodynamic overload states of the LV.…”
Section: Introductionmentioning
confidence: 98%
“…Six-week-old (150–200 g) male Wistar rats underwent shunting of the abdominal aorta and the inferior vena cava to induce chronic progressive volume overload for 24 weeks resulting in HF, as described earlier [ 10 , 11 ]. Briefly, anesthesia was induced by placing the animals in a chamber filled with 5% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…The Vivid I (GE Healthcare, Waukesha, WI, USA) echocardiographic imaging system equipped with the GE 12L-RS linear transducer (13 MHz) was used to non-invasively assess the temporal alterations in LV structure and function [ 10 , 11 ]. Prior to measurements, rats were anesthetized in a chamber with 5% isoflurane, then anesthesia was maintained by inhalation of 2% isoflurane (mixed in pure oxygen) from an insulated facemask, while placing the rats in a supine position on a controlled heating pad (maintaining core temperature at 37 ± 0.5 °C throughout the measurements).…”
Section: Methodsmentioning
confidence: 99%
“…Athletes with MR showed tendentially higher LV volumes; significantly higher LV GLS, LAVi max , and RAVi max ; and significantly lower RA total emptying fraction than athletes with no MR. Although such mild MR (assessed during resting conditions) certainly cannot be considered a hemodynamically relevant stimulus, these observations refer to what can be seen in the case of pathological LV volume overload (18,19). These findings can originate in two ways: 1) an athlete with a predisposition to a more pronounced exercise-induced chamber dilation may also be more prone to higher MA dimensions and a consequential MR, and 2) there is an inherent anatomical cause of the MR that may significantly increase during exercise, resulting in more excessive cardiac remodeling.…”
Section: Discussionmentioning
confidence: 77%